HALLONBACKEN A dementia village in Utby - DIMITRIADOU, CHRISTINA; PALMQVIST, EBBA; NYLIN, LUDWIG (My University, 2023)
THE SITE, UTBY NEARBY FUNCTIONS SECTIO N THROUGH THE AREA T h e p r o j e c t s i t e i s l o c a t e d i n U t b y, a n a r e a 6 k m e a s t o f t h e c i t y c e n t r e o f G o t h e n b u r g . T h e a r e a h a s g o o d connections to the city centre. T h e p l o t i s l o c a t e d i n t h e m i d d l e o f a r e s i d e n t i a l a r e a that is characterized by single-family houses and two s t o r e y b u i l d i n g s . I t i s a b e a u t i f u l p l a c e s u r r o u n d e d b y a l o t o f n a t u r e . I n t h e v i c i n i t y o f t h e p l o t t h e r e i s , a m o n g o t h e r t h i n g s , a l o c a l s h o p , s c h o o l , p r e s c h o o l , c h u r c h e s a n d p l a y g r o u n d s . T h e p l o t h a s a c h a l l e n g i n g t o p o g r a p h y w i t h h e i g h t d i f f e r e n c e s o f u p t o 2 0 m e t e r s . T h i s a l s o m e a n s t h a t t h e r e a r e n i c e v a n t a g e p o i n t s t h a t s t r e n g t h e n t h e c o n n e c t i o n w i t h n a t u r e . O n t h e p l o t t h e r e i s a l s o c u r r e n t l y a n a l l o t m e n t g a r d e n , w h i c h a c t a s a g a t h e r i n g point for the residents in the local community. T h e p u r p o s e o f t h e d e m e n t i a v i l l a g e i s t o c r e a t e a l i v i n g s i t u a t i o n w h e r e t h e r e s i d e n t f e e l s t h e i n d e p e n d e n c e o f h a v i n g t h e i r o w n h o m e a n d b e i n g a b l e t o m o v e f r e e l y w i t h i n t h e v i l l a g e , b u t a t t h e s a m e t i m e r e c e i v e t h e d a i l y help that’s needed. T h e m a i n g o a l o f t h e p r o j e c t i s t o d e s i g n a n a s s i s t e d l i v i n g f a c i l i t y i n U t b y. T h e f o c u s i s o n h e a l t h c a r e a r c h i t e c t u r e f o r e l d e r l y p e o p l e w i t h d e m e n t i a . T h e p r o g r a m p r o p o s e s a s t r u c t u r e f o r a p p r o x i m a t e l y 8 0 r e s i d e n t s w i t h a r e a s f o r s t a f f , t e c h n o l o g y a n d e s s e n t i a l functions.